I love you… but not unconditionally: Perceptions about luxury fashion brands - Magalhães, C. (2022)
The Generation Y (1978-2000) live in a constant change and are always interacting among them and the brands that they love. The current study aims to contribute to better understand the perceptions that Y's have about Corporate Social Responsibility in fashion luxury brands. Therefore, 31 in-depth interviews were conducted with a group of people belonging to Generation Y. The findings reveal that Y's are concerned about transparent procedures and helping business and society to improve as a consequence of their sustainable and responsible attitudes. The environmental issues and labour practices are the most cited, commented and recommended factors of corporate social responsibility (CSR) proposed by participants. The article provides a framework presenting the seven core factors to incorporate CSR.